Hadith Reception in the Spirituality of the Banjar Ethnic Community's Samman Dhikr Tradition - Tamimudin, Mohammad Mubaroqut; Hasan, Ubaidillah (UIN Sunan Gunung Djati Bandung, 2024)
The social phenomena in the masses make them have to interact with each other on the life as well as on the spirituality of a person; this makes the researchers interested in revealing the terminology of social society, in particular in the Banjarese at Village Dalem of Tulungagung, Indonesia, especially concerning the tradition of dzikir Samman. The focus of the research is the facts, and interpretation is done in a way that connects facts that have been studied by giving assumptions, the imagination of facts-facts that exist and compatibility with the subject of the study, so that from there can be found the interrelationship between facets. This research uses qualitative research methods using library studies; the theoretical approach used is Max Weber's sociological theory. The result of this research is this tradition as a container for social interaction of society as well as an approach to God. Implications of this study are expected to be a reference in shaping the soul of society and young people so as to avoid negative behavior that can make them better in the future.